2017
DOI: 10.2754/avb201786030231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of niacin supplementation on the insulin resistance in Holstein cows during early lactation

Abstract: Insulin resistance in early lactation includes low glucose concentration, low insulin release and responsiveness and high lipolysis. Niacin is important antilipolytic agent and leads to increase glucose and insulin concentration. The objectives of this study were to determine the influence of niacin on the insulin resistance in cows during early lactation using the difference of value and regression analysis between blood non-esterified fatty acid (NEFA), glucose and insulin concentrations, revised quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
2
9
1
Order By: Relevance
“…Plasma NEFA can be partially oxidised to form BHBA or esterified to be stored in the liver as TAG (39) . As expected, Hristovska et al (45) and Wei et al (46) found the plasma BHBA concentration decreased after niacin supplementation. Similar to plasma NEFA concentration, abomasal infusion of niacin Horner et al (25) 6 g NA/d --↑ N/A ↑ -Erickson et al (26) 12 (24) 12 g NA/d ------Christensen et al (27) 12 (28) 6 g NA/d --↑ ---Kumar & Dass (29) 100 mg NA/kg feed (30) 6 g NA/d --↑ -↑ -Niehoff et al (13) 6 g NA/d ↓ ↑ N/A ↓ --Luo et al (31) 320 mg NA/kg feed decreased plasma BHBA concentration, and the rebound of plasma BHBA concentration after termination of infusion was found in feed-restricted dairy cows (50,51) .…”
Section: Metabolic Statussupporting
confidence: 71%
See 2 more Smart Citations
“…Plasma NEFA can be partially oxidised to form BHBA or esterified to be stored in the liver as TAG (39) . As expected, Hristovska et al (45) and Wei et al (46) found the plasma BHBA concentration decreased after niacin supplementation. Similar to plasma NEFA concentration, abomasal infusion of niacin Horner et al (25) 6 g NA/d --↑ N/A ↑ -Erickson et al (26) 12 (24) 12 g NA/d ------Christensen et al (27) 12 (28) 6 g NA/d --↑ ---Kumar & Dass (29) 100 mg NA/kg feed (30) 6 g NA/d --↑ -↑ -Niehoff et al (13) 6 g NA/d ↓ ↑ N/A ↓ --Luo et al (31) 320 mg NA/kg feed decreased plasma BHBA concentration, and the rebound of plasma BHBA concentration after termination of infusion was found in feed-restricted dairy cows (50,51) .…”
Section: Metabolic Statussupporting
confidence: 71%
“…It is likely that niacin supplementation level may play a role in the antilipolytic effect in dairy cows. In early lactation, the relatively low dosages of free nicotinic acid or nicotinamide supplementation (6-24 g/d) in studies summarised by Niehoff et al (5) and two more recent studies (47,48) demonstrated only minor effects, whereas 12 g/d of RPN (16,44) , 45 g/d of nicotinamide (46) or 120 g/d of nicotinic acid (45) supplementation demonstrated a greater influence on plasma NEFA concentration. The extensive degradation of free niacin in the rumen may partly explain the lack of effects when a low level of nicotinic acid was supplemented.…”
Section: Metabolic Statusmentioning
confidence: 98%
See 1 more Smart Citation
“…Treatment with niacin caused dual changes in insulin resistance: decreased NEFA concentrations led to a decrease in insulin resistance (due to an increase in both insulin efficiency and the insulin sensitivity index), but increased concentrations of insulin and glucose possibly caused an increase in insulin resistance in dairy cows (due to the lower insulin sensitivity index and possibly lower antilipolytic effects of insulin) (Hristovska et al, 2017).…”
Section: Insulin Resistance Definition and Pathogenesismentioning
confidence: 99%
“…Also, the RQUICKI is highly determined by NEFA during early lactation (CINCOVIĆ et al, 2014). HRISTOVSKA et al (2017) showed that NEFA and RQUICKI were in strong linear correlation, and in cows with a lower RQUICKI index, lower NEFA concentrations after application of niacin as an antilipolytic vitamin were established. Intravenous infusion of fat emulsion caused development of insulin resistance in Holstein-Frisian cows (PIRES et al, 2007).…”
Section: Discussionmentioning
confidence: 96%